THE ACTIVITY OF ANTIOXIDANT ENZYMES IN RAT SCIATIC NERVE FOLLOWING A HEMORRHAGIC STROKE - Dovgan, I.M.; Melnyk, N.O.; Labunets, I.F.; Utko, N.A.; Savosko, S.I. (World of Medicine and Biology, 2017)
Stroke is characterized by structural and biochemical disruptions in the brain. Anterograd degeneration in the spinal cord and sciatic nerve was found against stroke. Biochemical changes of this processes are still unstudied. The purpose of study – to determine changes in the activity of enzymes of antioxidant system in the sciatic nerve after cerebral stroke modeling and drug administration (piracetam, quercetin, lipin) in experimental study. Materials and methods. Experimental studies were conducted on 45 male rats WKY line (average weight 220-250 g). Hemorrhagic stroke was modeled in the right hemisphere of the brain by introducing autoblood in internal capsule. Drugs were injected intraperitoneally (i.p.) in 2 hours after stroke simulation: piracetam (100 mg/kg, 10 days), quercetin (7,2 mg/kg, 5 days), lipin (lecithin) (10 mg/kg, 5 days). In 10 days after a stroke simulation the activity of superoxide dismutase, catalase, glutathione peroxidase and glutathione reductase was evaluated. The demyelination of nerve fibers in the sciatic nerve was evaluated by histological methods. Results. Demyelination of nerve fibers and Schwann cells activation in the sciatic nerve, activation of superoxide dismutase were registered in rats on the 10th day after the stroke. The piracetam, quercetin and lipin injection caused increased activity of superoxide dismutase, glutathione peroxidase and glutathione reductase. In the combined administration of the drugs the level of the activity of the enzymes of glutathione metabolism (glutathione peroxidase, glutathione reductase) had no statistically significant difference compared to the control group. Conclusions. Development of demyelination in the sciatic nerve, accompanied by changes in enzymes activity of the antioxidant system was found against the stroke. The use of drugs with antioxidant action may reduse the development of these disorders.